Randomised controlled crossover trial of the effect on Ptco2 of oxygen-driven versus air-driven nebulisers in severe chronic obstructive pulmonary disease. Issue 11 (8th December 2011) - Edwards, Llifon; Perrin, Kyle; Williams, Mathew; Weatherall, Mark; Beasley, Richard
Abstract : Background: The comparative safety of oxygen versus air-driven nebulised bronchodilators in patients with acute exacerbations of chronic obstructive pulmonary disease (COPD) is uncertain. A randomised controlled trial was performed to assess the effect on the arterial partial pressure of carbon dioxide of nebulised bronchodilator driven with oxygen versus air in stable severe COPD. Methods: In an open label randomised study, 18 subjects with stable severe COPD attended on 2 days to receive nebulised bronchodilator therapy driven by air or oxygen. Subjects received 5 mg salbutamol and 0.5 mg ipratropium bromide by nebulisation over 15 min, then, after 5 min, 5 mg salbutamol nebulised over 15 min, followed by 15 min of observation. Transcutaneous carbon dioxide tension (Ptco 2 ) and oxygen saturations were recorded at 5 min intervals during the study. The primary outcome was the Ptco 2 after the completion of the second bronchodilator treatment. Results: Ptco 2 was higher with nebulised bronchodilator therapy delivered by oxygen, but decreased back to the level associated with air nebulisation 15 min after completion of the second nebulised dose. One subject experienced an increase in Ptco 2 of 11 mm Hg after the first bronchodilator nebulisation driven by oxygen. The mean Ptco 2 difference between the oxygen and air groups after the second nebulisation was 3.1 mm Hg (95% CI 1.6 to 4.5, p<0.001). Conclusion: Nebulisers driven with oxygen result in significantly higher levels of Ptco 2 than those driven with air in patients with severe COPD. Clinical trial registration number: The study was registered on the Australian New Zealand Clinical Trials Registry (ACTRN12610000080022).